Accountability and Transparency of Boss Funds: An Overview of Financial Management in Public Schools - Rizka, Annissa Fitriani; Ahmad, Masduki; Rochimah, Heni (Journal of English Language and Education, 2025)
The School Operational Assistance (BOS) Fund serves as one of the primary fiscal instruments in Indonesia to support the operational needs of public schools. This study aims to evaluate the implementation of accountability and transparency principles in BOS fund management based on a comprehensive literature review of relevant studies and government regulations over the past decade. The findings reveal that while schools have generally complied with accountability standards such as budgeting, reporting, and internal oversight mechanisms, the implementation of transparency remains inconsistent. Limitations in information dissemination, financial literacy, and stakeholder engagement have hindered broader public monitoring and trust. This study concludes that enhancing the capacity of school financial managers, establishing accessible and inclusive information systems, and reinforcing community participation are strategic efforts needed to improve BOS fund governance. These findings are expected to inform future education finance policies aimed at achieving more accountable and transparent school financial systems.